CONSIDERATIONS FOR SURGICAL APPROACHES TO DEROTATIONAL HUMERAL OSTEOTOMY IN BOTH OBSTETRIC AND ADULT TRAUMATIC BRACHIAL PLEXUS INJURIES - Ivalde, Flavio César; Marazita-Valverde, Jose; Bataglia, Danilo (Journal of Ayub Medical College Abbottabad, 2020)
In brachial plexus birth palsy (C5-C6/C5-C6-C7), about 66-92% of patients will have a spontaneous recovery, but the remaining patients may develop some grade of structural or functional sequela, or it can even impact on neuronal plasticity. But in adults after high-energy accidents such as motor-vehicle accidents, in which there can be devastating consequences. A derotational humeral osteotomy is an option for dealing with the sequelae of obstetric and traumatic brachial palsy in adults with external rotation deficit. Three approaches have been described: deltopectoral, medial, and percutaneous. However, to the best of our knowledge, no previous research has investigated the differences among the surgical approaches. We aim to highlight the characteristics of each issue that is described above and discuss our preference. In conclusion, the literature reports that all three approaches provide good functional outcomes to restore hand-face plane of movement. We suggest that the selection of each access should depend on previous nerve reconstruction surgeries, muscle tropism, and the severity of soft tissue retraction. Keywords: brachial plexus; Iatrogenic injuries; shoulder; surgical exposures; Humeral Osteotomy; Deltopectoral approach